Severe Hypocalcemia and Hypomagnesemia with Denosumab in Advanced Chronic Kidney Disease: Case Report and Literature Review - Christina F. Marlow; Shailendra Sharma; Faizan Babar; Jianqing Lin (Case Reports in Oncological Medicine)
Background. Denosumab has become the preferred agent over zolendronic acid to help prevent skeletal-related events in patients with metastatic bone disease and multiple myeloma because it is approved for use in those with kidney dysfunction. However, denosumab has been linked to cases of hypocalcemia, particularly in those with advanced kidney disease. Case Presentation. We present the case of a patient with metastatic prostate cancer and chronic kidney disease due to obstructive nephropathy who developed severe hypocalcemia and hypomagnesemia after denosumab injection, which required intensive care unit admission, aggressive calcium supplementation, and hemodialysis assistance. We reviewed the evidence behind the safety profile of denosumab in chronic kidney disease, and we also looked at additional factors that may precipitate severe hypocalcemia with denosumab in advanced kidney disease. Conclusion. We believe that denosumab should be avoided in advanced chronic kidney disease due to the potential life-threatening, severe hypocalcemia that has been observed.